Pembentukan Karakter Dermawan Siswa melalui Pembiasaan Infak dan Sedekah di MTsN 7 Pasaman Barat - Syari'ah; Mustafa (ALSYS, 2026)
Although character education through religious habituation has been widely implemented in Islamic schools, studies specifically examining the development of generous character through the habituation of infaq and sadaqah at the Madrasah Tsanawiyah level remain limited. This study aims to describe the process of developing students’ generous character through the habituation of infaq and sadaqah and to identify its supporting and inhibiting factors at MTsN 7 Pasaman Barat. The study employed a qualitative approach with a descriptive field research design. Data were collected through observation, interviews, and documentation from March to April 2026, involving the madrasah principal, homeroom teachers, Akidah Akhlak teachers, Fiqh teachers, Islamic Cultural History teachers, and eighth-grade students as informants. The data were analyzed thematically following the stages proposed by Miles and Huberman, including data reduction, data presentation, and conclusion drawing and verification, while data validity was examined through source, method, and time triangulation. The results showed that students’ generous character was developed through five interrelated efforts: exemplary conduct by the madrasah principal and teachers, habituation through direct experience, the inculcation of generosity values, the provision of appreciation, and parental involvement. Supporting factors included the commitment of the madrasah principal and teachers, well-planned and sustainable madrasah programs, the availability of facilities, and parental support. Inhibiting factors included program management that had not yet been optimally systematized and students’ intrinsic awareness that had not fully developed. This study concludes that the habituation of infaq and sadaqah, when implemented in a structured and consistent manner and supported by exemplary conduct and parental involvement, can strengthen the development of students’ generous character. Theoretically, these findings extend the application of social learning and moral action theories within the context of Islamic philanthropy in madrasahs, while practically, they provide a basis for madrasah leaders to design more systematic, measurable, and sustainable habituation programs. Future research is recommended to involve a broader range of participants and employ long-term evaluation instruments.